2020
DOI: 10.1080/21622671.2020.1837222
|View full text |Cite
|
Sign up to set email alerts
|

Brexit geographies of transnational education: uncertainty, ‘global Britain’ and European (re-)integration

Abstract: Higher education in the UK constitutes an important (export) sector that depends on mobilities of capital, labour and students. This article contributes to 'Brexit geographies' by exploring how the economic geographies of British transnational education are reconfigured during uncertainty over Brexit through spatial strategies of universities. Based on qualitative research and in-depth interviews with decisionmakers in higher education in the UK, it maps the investments and analyses the rationales, narratives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Following the renewed salience of the EU-UK border, firms have started to re-evaluate the division of labour between UK-based subsidiaries and the European mainland (Fuller, 2021). The financial sector has relocated activities to the EU in order to be able to continue their operations (Heneghan and Hall, 2021), as have several British universities (Kleibert, 2020). Global value chains, while heavily affected by the new regulations, do not cease to exist but morph into new forms and in-and exclude different territories.…”
Section: Shoring Up the Archipelago And The Quadruple Challenge To Gl...mentioning
confidence: 99%
“…Following the renewed salience of the EU-UK border, firms have started to re-evaluate the division of labour between UK-based subsidiaries and the European mainland (Fuller, 2021). The financial sector has relocated activities to the EU in order to be able to continue their operations (Heneghan and Hall, 2021), as have several British universities (Kleibert, 2020). Global value chains, while heavily affected by the new regulations, do not cease to exist but morph into new forms and in-and exclude different territories.…”
Section: Shoring Up the Archipelago And The Quadruple Challenge To Gl...mentioning
confidence: 99%
“…A survey conducted in late 2020 of senior UK university managers responsible for international education reported that half thought that they were likely to expand TNE in response to the pandemic (Universities UK, 2020). Similarly, four out of 12 university managers who were interviewed about their likely offshore campus strategies in the EU post Brexit stated that they planned to establish or expand OBC provision (Leibert, 2020 ). The pandemic is also seen as providing a major stimulus to ODL with some countries relaxing online regulations in response to the pandemic most notably China.…”
Section: The Brexit and Covid Shocksmentioning
confidence: 99%
“… 8 A few articles discuss the possible impacts of Brexit on offshore enrolment but provide no hard data (see Courtois and Veiga 2020 and Leibert 2020 ). Only one article could be located on the impact of Covid on offshore provision in a developing country, namely Vietnam.…”
mentioning
confidence: 99%